Case Report: Pediatric Malignant Atrophic Papulosis With Small Bowel Perforation and Positivity of Anticardiolipin Antibody - Hai-Qing Wang; Yu Guan; Xiao-Pan Gong; You-Tao Chen; Chao Ji (Frontiers Media S.A., 2021)
Malignant atrophic papulosis (MAP) is a life-threatening vasculopathy affecting the skin, gastrointestinal tract, central nervous system, pleural membrane, and pericardium. MAP carries a poor prognosis primarily because of its systemic involvement. It is extremely rare in children. Herein, we report a pediatric case of MAP with small bowel perforation and anticardiolipin antibody positivity.